(untitled) (KULT_online, 2014)
In recent years, the interest in methods of empirical research has been consistently increasing. Methodological knowledge is all but a prerequisite for writing academic papers. The anthology Fremdsprachenunterricht empirisch erforschen. Grundlagen – Methoden – Anwendung provides profound insights into the issues of foreign language research by illustrating the different stages of the research process with selected methodical examples. The publication offers theoretically based depictions for the planning of empirical studies and elaborates important instruments of data collection and analysis. By presenting detailed examples of implementation the authors highlight the potential of qualitative and quantitative research projects.